CLINICAL AND PARACLINICAL CHARACTERISTICS AND PATIENT CARE OUTCOMES LUMBAR SPONDYLOLISTHESIS SURGERY AT 108 CENTRAL MILITARY HOSPITAL IN 2025 (Tạp chí Y học Cộng đồng, 2026)
Objective: To describe clinical and paraclinical characteristics and evaluate the outcomes of nursing care for patients undergoing lumbar spondylolisthesis surgery at the 108 Military Central Hospital in 2025.Methods: A cross-sectional descriptive study was conducted on patients diagnosed with lumbar spondylolisthesis who underwent surgery at the Spine surgery department, 108 Military central Hospital. Data was collected from medical records and through a self-designed interview tool to assess nursing care effectiveness based on the Oswestry Disability Index (ODI), the Visual Analog Scale (VAS) for pain assessment, and patient satisfaction with nursing care outcomes. Data was analyzed using SPSS 25.0 with frequency tables and percentage distributions.Results: The mean age of participants was relatively high (61.7 ± 8.9 years), with a male-to-female ratio of 1:4.3. The average length of hospital stay was 5.8 ± 2.0 days. Pain was the primary reason for admission in 95% of cases. A total of 83.5% of patients experienced painless dressing changes, and the standard dressing change frequency of every two days was achieved in 95.5% of cases. The proportion of patients whose surgical drains were removed within 48 hours was high (96.0%), and more than half did not require urinary catheterization after surgery (58.5%). The incidence of nerve root injury and surgical site infection were 3.5% and 1.0%, respectively. All patients reported satisfaction with surgical nursing rehabilitation activities, with 55.7% being very satisfied, 25.8% satisfied, and 15.5% neutral.Conclusion: The postoperative complication rate was very low (4.5%), and 100% of patients expressed satisfaction with nursing care at varying levels. The proportion of patients with good care outcomes was very high (86.5%).
Keywords: Lumbar spondylolisthesis surgery, nursing care, 108 Military Central Hospital